AN ANALYSIS OF STUDENTS’ SPEAKING SKILL IN STORYTELLING AT SECOND SEMESTER OF STIE-SAK ACADEMIC YEAR 2025/2026 - Sukarta Kartawijaya wijaya; Jeke Jufitra; Al-Padli Al-Padli (The Future of Education Journal, 2026)
This research was done in order to get description about students’ skill in storytelling. The researcher would analyze and describe the students’ speaking skill of the second semester students at STIE-SAK academic year 2025/2026. This research was descriptive research, and the population in this research was all of the second semester students at TIE-SAK. There were some classes of second semester students at STIE-SAK which was homogeny and they were taught by the same lecturer so the researcher needed to choose the sample of the research by using cluster sampling. The instrument in this research was speaking test. Test was collected from the students’ performance of their speaking. They were asked to speak in English and they would tell story based on their experience in front of the class one by one, and the researcher would record it and then analyzed the test by using speaking scoring rubric to see the students’ ability in storytelling. Based on the finding of the research, the researcher gets conclusion that the students’ skill in storytelling of the second semester students at STIE-SAK academic year 2025/2026 was low. The data has proved that the students had low speaking ability. There were four students got A or it was about 14,28% of them got very good score. There were 7 students got B or (25%, 6 students got C, 3 students got D, and there were 8 students got E. It could be said the students at the second semester students at STIE-SAK had low speaking ability.